Physicochemical characterization of the DNA complexes with different surfactants. (19th November 2021) - Radko, Aleksandra; Lalik, Sebastian; Deptuch, Aleksandra; Jaworska-Gołąb, Teresa; Ekiert, Robert; Górska, Natalia; Makyła-Juzak, Katarzyna; Nizioł, Jacek; Marzec, Monika
Abstract: DNA complexes with cetyltrimethylammonium chloride (CTMA), benzyldimethylhexadecylammonium chloride (BAC) and hexadecylpyridinium chloride (HDP) surfactants as powder samples were studied by Fourier-transform middle infrared spectroscopy, X-ray diffraction and dielectric spectroscopy methods. Complexation as electrostatic interactions was confirmed by FT-MIR spectroscopy. The width of DNA-surfactant complexes was estimated to 61–73 Å based on modeling with the semi-empirical PM7 method. Based on SAXS results we propose the packing model for the complex molecules as hexagonal or slightly distorted hexagonal depending on the surfactant. For the first time the dielectric process registered in the low frequency range for all complexes was interpreted as oscillation of surfactant ions (BAC +, HDP + or CTMA + ), analogous to the oscillation of ions (e.g. Na + ) in solutions of pure DNA. The influence of the structure of the complex-forming surfactant molecule on the value of the relaxation time distribution parameter is discussed. Graphical abstract: Image 1 Highlights: Native DNA is mainly characterized by B-conformation, while in complexes with surfactants it has A-conformation. DNA-CTMA complex have a hexagonal structure, while DNA-BAC and DNA-HDP a slightly distorted hexagonal structure. The relaxation process for DNA-surfactant complexes is connected with the oscillations of the surfactant functional groups.